Antidiabetic effect of a novel non-thiazolidinedione PPAR big gamma/alpha agonist on ob/ob mice - Hu Xi; Feng Ying; Shen Yu; Zhao Xiao-feng; Yu Juan-hong; Yang Yu-she; Leng Ying (Acta Pharmacologica Sinica, 2016)
Aim: To study whether T33, a new synthesized non-thiazolidinedione (TZD) peroxisome proliferator-activated receptor (PPAR) gamma/alpha dual agonist has an antidiabetic effect on ob/ob mice. Methods: Ob/ob mice were treated with 4 mg/kg or 8 mg/kg T33 by gavage for 20 d. Blood glucose levels were measured regularly. An oral glucose tolerance test (OGTT) and an insulin tolerance test (ITT) were preformed on d 8 and d 12, respectively. The levels of insulin, triglyceride and free fatty acid (FFA) in the serum were measured at the end of administration. The intramuscular and liver triglyceride content was also determined. Results: T33 reduced the hyperglycemia, hyperinsulinemia and hyperlipidemia of the ob/ob mice. The OGTT and ITT showed that the insulin resistance state of the ob/ob mice was obviously ameliorated after T33 treatment. After 20 d treatment with 8 mg/kg T33, the triglyceride content in the gastrocnemius muscle decreased significantly. T33 did not have any effect on triglyceride content in the liver, whereas rosiglitazone significantly increased the hepatocyte lipid deposition. Conclusion: The PPARgamma/alpha dual agonist T33 has antidiabetic and insulin-sensitizing effects in ob/ob mice. It has the potential to be a new therapeutic candidate for the treatment of type 2 diabetes.